2018
DOI: 10.18410/jebmh/2018/430
|View full text |Cite
|
Sign up to set email alerts
|

Smart Phone Based Teleophthalmological Services of MKCG McH, Berhampur

Abstract: BACKGROUNDThe rural citizens who constitute major portion of Indian population are underprivileged as they have very little or no access to tertiary eye care. In order to make eye care services accessible to everyone, the concept called teleophthalmology has come into existence. A mobile van with eye-care-experts and equipment regularly reconnoiters through the rural population in the district of Ganjam to carry out screening, offsite diagnosis, monitoring, providing treatment and distantly educate the paramed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 21 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…However, Figure 5 (b) revealed that the population density and biomass of four sectors showed major differences between northern sector and outer channel area. The NMDS study further revealed that the entire lake acts as three different units (Mahapatro, 2017) during tropical cyclone condition. First the fresh water province (northern sector), second is the marine province (outer channel area) and third one is the brackish water unit (central and southern sector).…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…However, Figure 5 (b) revealed that the population density and biomass of four sectors showed major differences between northern sector and outer channel area. The NMDS study further revealed that the entire lake acts as three different units (Mahapatro, 2017) during tropical cyclone condition. First the fresh water province (northern sector), second is the marine province (outer channel area) and third one is the brackish water unit (central and southern sector).…”
Section: Resultsmentioning
confidence: 88%
“…According to Mahapatro (2017), Mahapatro and Kadam (2018), and Mahapatro et al (2021), the outer channel of Chilika is a highly biodiversity rich province since it harbors numerous microhabitats such as (i) sea grass & seaweed bed, (ii) molluscan reef bed, (iii) mangrove vegetation, (iv) sand dune vegetation, (v) intertidal mudflats, (vi) subtidal shallow region, and (vii) diminutive creeks. Combination of all these microhabitats within the outer channel area provides immense habitat support for the congregation of wide range of flora & fauna (Mahapatro, 2017;Mahapatro andKadam 2018, &Mahapatro et al, 2021).…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations